Seven insecure academic conditions for students as a basis for implementing teacher professional learning - Hartini, Sri; Mulyana , Ade Rendi; Abidah, Jilan; Sabri, Farhana (Universitas Ahmad Dahlan, 2023)
Student academic performance as a measure of future success. Students who can develop academic performance in the classroom and outside the school are a big part of the success process. However, some children have academic insecurity problems that impact academic performance and may influence future success. Professional teachers must be able to analyze students in this condition. This research aims to analyze students' educational insecurity conditions using seven indicators—a quantitative study with a survey with random sampling on 521 students at school. The academic insecurity scale distributed to students randomly was analyzed through percentages and standard deviations with four categories: very high, high, low, and very low. The results of the research show that the average student's insecure academic condition is in a standard category on seven indicators: students do not want to get out of their comfort zone, like to compare themselves with other individuals, look down on themselves, have to get praise and recognition from other individuals, avoid interaction with the surrounding environment, experiencing failure, and lack of gratitude. Then, 54% of students have an insecure academic condition in the low category and 14% in the shallow category. Academic insecurity is also in the high category at 29% and very high at 3%. The high and very high categories require significant attention from schools and teachers at schools with exceptional handling. Professional teachers must be able to implement fair and enjoyable learning to prevent gaps who experience academic insecurity because they do not receive proper appreciation in the teaching.